Generation of Stilbene Glycoside with Promising Cell Rejuvenation Activity through Biotransformation by the Entomopathogenic Fungus Beauveria bassiana - Sang Keun Ha; Min Cheol Kang; Seulah Lee; Om Darlami; Dongyun Shin; Inwook Choi; Ki Hyun Kim; Sun Yeou Kim (Biomedicines, 2021)
A stilbene glycoside (resvebassianol A) (1) with a unique sugar unit, 4-O-methyl-D-glucopyranose, was identified through biotransformation of resveratrol (RSV) by the entomopathogenic fungus Beauveria bassiana to obtain a superior RSV metabolite with enhanced safety. Its structure, including its absolute configurations, was determined using spectroscopic data, HRESIMS, and chemical reactions. Microarray analysis showed that the expression levels of filaggrin, HAS2-AS1, and CERS3 were higher, while those of IL23A, IL1A, and CXCL8 were lower in the resvebassianol A-treated group than in the RSV-treated group, as confirmed by qRT-PCR. Compound 1 exhibited the same regenerative and anti-inflammatory effects as RSV with no cytotoxicity in skin keratinocytes and TNF-α/IFN-γ-stimulated HIEC-6 cells, suggesting that compound 1 is a safe and stable methylglycosylated RSV. Our findings suggest that our biotransformation method can be an efficient biosynthetic platform for producing a broad range of natural glycosides with enhanced safety.